Natural enemies of Bemisia tabaci (Gennadius) B biotype and Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae) in Brasília, Brazil - Oliveira,Maria R.V. de (2003)
A survey was conducted in Brasília, DF, from January 1999 to March 2001, on tobacco, cotton, tomato, cabbage, soybean, bean, melon, eggplant and the weed Emilia sonchifolia DC, to collect natural enemies of the whiteflies Bemisia tabaci (Gennadius) and Trialeurodes vaporariorum (Westwood). Fourteen predators, twelve parasitoids and two hyperparasitoids were collected. Among the parasitoids, Encarsia inaron (Walker) is recorded for the first time in South America, and E. basicincta Gahan is a new record for Brazil. E. aleurothrixi Evans & Polaszek is recorded for the first time parasitizing B. tabaci. The lady beetles Nephaspis hydra Gordon and Delphastus davidsoni Gordon are registered for the first time preying on B. tabaci.